The Influenza A Virus H3N2 Triggers the Hypersusceptibility of Airway Inflammatory Response via Activating the lncRNA TUG1/miR-145-5p/NF-κB Pathway in COPD - Tu, You-Hui; Guo, Yan; Ji, Shuang; Shen, Ji-Long; Fei, Guang-He (Frontiers in Pharmacology, 2021)
Background: Patients with chronic obstructive pulmonary disease (COPD) are more susceptible to Influenza A virus (IAV) with more severe symptoms, yet the underlying molecular mechanisms of the hypersusceptibility of airway inflammatory response remain unclear. Methods: The primary human bronchial epithelial cells (pHBECs) were isolated from normal and COPD bronchial tissues (NHBE and DHBE) and cultured with/without IAV infection in vitro. DHBE cells were exposed to IAV for 24 hours after knockdown lncRNA TUG1 with short hairpin RNA (shRNA). Gain-of-function assays were performed with miR-145-5p inhibitor and NF-κBp65 transfection. The expressions of lncRNA TUG1, miR-145-5p, phospho-NF-κBp65, NF-κBp65, TNF-α and (Interleukin) IL-1β were examined with qRT-PCR, Western Blotting and ELISA. The interactions of lncRNA TUG1, miR-145-5p and NF-κB were verified with Luciferase reporter assay. Results: The expressions of lncRNA TUG1, phospho-NF-κBp65, TNF-α and IL-1β were increased significantly in pHBECs after infected with IAV for 24 hours (all P＜0.05). The detailed time analysis revealed that the NF-κBp65 in DHBE was activated earlier than that in NHBE by Western Blotting and Immunofluorescence. Knockdown of lncRNA TUG1 and miR-145-5p mimic attenuated the expressions of NF-κBp65, TNF-α and IL-1β significantly. The miR-145-5p inhibitor and NF-κBp65 transfection reversed the attenuated expressions of NF-κBp65, TNF-α and IL-1β. Conclusion: The IAV causes the hypersusceptibility of airway inflammatory response, which may be closely associated with more severe symptoms in AECOPD patients. The lncRNA TUG1 inhibitor may be a promising therapeutic strategy for AECOPD caused by IAV.